A co-gestão como estratégia de governança da pesca artesanal em rios amazônicos barrados por hidrelétricas - Figueiredo, Ellen Silvia Amaral (Universidade Federal do Tocantins, 2021)
Artisanal fishing is regarded as an important source of food and income for an expressive part of the population of developing countries under the condition of social vulnerability. However, the sustainability of this activity is threatened by the current development model that causes the water pollution of rivers and the significant alteration of the aquatic ecosystem. The installation of large infrastructure works, such as hydroelectric dams constitutes one of the main threats to biodiverdity in tropical rivers, such as Amazonas. The negative effects of such works surpass ecological issues, directly affecting the human population that depends on the fishing resources for its survival. The change or interruption of fishing generates countless other social effects, such as the decrease in income and the compromise of the food security of the involved population. In Brazil, in the case of the Paraná River basin, even with considerable evidence of the negative impacts caused to fishing due to the installation of numerous dams in the last 40 years, little has progressed in the subject of compensatory measures for fishermen impacted by Dams and fishermen follow at the margins of public policy. If the impacts generated by hydroelectric dams were harmful to fishermen in the southeastern region of the country, what dimension would they reach in the region with the highest consumption of fish per capita in the country, such as the Amazon region? Are there alternatives to promoting the sustainability of artisanal fisheries even in environments with such a disturbance? These questions lead to the central question of the thesis: What governance arrangements would enable the greater sustainability of fisheries in these environments, considering management as a key process for the conservation of fisheries resources and the governmental strategy to use the Amazon Basin as a producer of megawatts? To address the theme of fisheries management as a promoter of sustainability, the present thesis introduces the theories of Common Pool Resources and Participatory Management, proposed by Elinor Ostrom and Berkes. To this end, the thesis is organized in three chapters besides the general introduction and conclusion. The first chapter presents a systematic review and analysis of the level of scientific knowledge available on fishing in environments impacted by hydroelectric power plants. Chapter 2, in turn, develops and tests a tool to assess the quality of environmental studies, identifying and proposing issues to be investigated or improved. Chapter 3 seeks, in the literature on participatory management in Brazil, the theoretical and methodological bases of existing experiences in Brazil, identifying and reflecting on the opportunities and obstacles to its implementation in the context of hydroelectric dams. Subsequently, in the general conclusion, the theoretical-analytical link of the chapters is presented, pointing out proposals for mitigating actions for socio-environmental impacts.